A plan of the city and harbour of Havanna, capital of island of Cuba. (1762)
Diagrams represent the city and harbour of Havanna, Cuba. It includes an explanation of places.
Level 2 deterioration.
Special Collections Floor.
Keywords: Cartographic material; Cuba; Havanna -- Cuba; Maps